Chemokine Receptor Expression on Normal Blood CD56+ NK-Cells Elucidates Cell Partners That Comigrate during the Innate and Adaptive Immune Responses and Identifies a Transitional NK-Cell Population - Margarida Lima; Magdalena Leander; Marlene Santos; Ana Helena Santos; Catarina Lau; Maria Luís Queirós; Marta Gonçalves; Sónia Fonseca; João Moura; Maria dos Anjos Teixeira; Alberto Orfao (Journal of Immunology Research)
Studies of chemokine receptors (CKR) in natural killer- (NK-) cells have already been published, but only a few gave detailed information on its differential expression on blood NK-cell subsets. We report on the expression of the inflammatory and homeostatic CKR on normal blood CD56+low CD16+ and CD56+high  CD16-/+low NK-cells. Conventional CD56+low and CD56+high NK-cells present in the normal PB do express CKR for inflammatory cytokines, although with different patterns CD56+low NK-cells are mainly CXCR1/CXCR2+ and CXCR3/CCR5−/+, whereas mostly CD56+high NK-cells are CXCR1/CXCR2− and CXCR3/CCR5+. Both NK-cell subsets have variable CXCR4 expression and are CCR4− and CCR6−. The CKR repertoire of the CD56+low NK-cells approaches to that of neutrophils, whereas the CKR repertoire of the CD56+high NK-cells mimics that of Th1+ T cells, suggesting that these cells are prepared to migrate into inflamed tissues at different phases of the immune response. In addition, we describe a subpopulation of NK-cells with intermediate levels of CD56 expression, which we named CD56+int NK-cells. These NK-cells are CXCR3/CCR5+, they have intermediate levels of expression of CD16, CD62L, CD94, and CD122, and they are CD57− and CD158a−. In view of their phenotypic features, we hypothesize that they correspond to a transitional stage, between the well-known CD56+high and CD56+low NK-cells populations.